KANDUNGAN TIMBAL (Pb) PADA TANAMAN PENEDUH DI JALAN TUANKU TAMBUSAI KOTA PEKANBARU - Ningrum, Indah Sulistyo; Yoza, Defri; Arlita, Tuti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
The increased number of vehicles are getting bigger every year, including in Pekanbaru. One of the air pollution sources come from vehicle. The exhaust from vehicle contains harmful heavy metals, for example is the lead. Tuanku Tambusai Street (Nangka Street) is one of the crowded streets in Pekanbaru which have a quite large heavy metals that emitted into the air. Lead is harmful to human health and the environment, so shade plants needs to be planted as bio-indicators. However, not all plants have the same ability to absorb the lead. This study aims to determine the amount of lead content in shade plants on Tuanku Tambusai street, in Pekanbaru city and to know the type of shade plants and canopy strata that most absorb to the lead. This study uses a Wet Ashing Method for the destruction the sample, then it is analyzed using Atomic Absorption Spectrophotometer (AAS). The results shows that the leaf Polyalthia longifolia Bent. & Hook. F. is 1.88 µg/g higher than Pterocarpus indicus Willd. 1.57 µg/g and Swietenia macrophylla 1.16 µg/g. Lead content in the middle of the canopy strata (1.72 µg/g) is higher than the content of lead in the bottom of the canopy strata (1.52 µg/g) and the upper canopy strata (1.38 µg/g). Keywords: lead, shade plants, Polyalthia longifolia, Pterocarpus indicus, Swietenia macrophylla